Benefits in cardiac function by CD38 suppression: Improvement in NAD+ levels, exercise capacity, heart rate variability and protection against catecholamine-induced ventricular arrhythmias - Agorrody, Guillermo (2022)
CD38 enzymatic activity regulates NAD+ and cADPR levels in mammalian tissues, and therefore has a prominent role in cellular metabolism and calcium homeostasis. Consequently, it is reasonable to hypothesize about its involvement in cardiovascular physiology as well as in heart related pathological conditions. Aim: To investigate the role of CD38 in cardiovascular performance, and its involvement in cardiac electrophysiology and calcium-handling. Methods and results: When submitted to a treadmill exhaustion test, a way of evaluating cardiovascular performance, adult male CD38KO mice showed better exercise capacity. This benefit was also obtained in genetically modified mice with catalytically inactive (CI) CD38 and in WT mice treated with antibody 68 (Ab68) which blocks CD38 activity. Hearts from these 3 groups (CD38KO, CD38CI and Ab68) showed increased NAD+ levels. When CD38KO mice were treated with FK866 which inhibits NAD+ biosynthesis, exercise capacity as well as NAD+ in heart tissue decreased to WT levels. Electrocardiograms of conscious unrestrained CD38KO and CD38CI mice showed lower basal heart rates and higher heart rate variability than WT mice. Although inactivation of CD38 in mice resulted in increased SERCA2a expression in the heart, the frequency of spontaneous calcium release from the sarcoplasmic reticulum under stressful conditions (high extracellular calcium concentration) was lower in CD38KO ventricular myocytes. When mice were challenged with caffeine-epinephrine, CD38KO mice had a lower incidence of bidirectional ventricular tachycardia when compared to WT ones. Conclusion: CD38 inhibition improves exercise performance by regulating NAD+ homeostasis. CD38 is involved in cardiovascular function since its genetic ablation decreases basal heart rate, increases heart rate variability and alters calcium handling in a way that protects mice from developing catecholamine induced ventricular arrhythmias.